التأويل في كتاب نقد الشعر - الربيعي، حامد بن صالح (جامعة عين شمس - كلية الآداب, 2012)
عنوان هذا البحث نيته وطموحه نحو الانتماء إلى ما يمكن تسميته جمالية التلقي في التفكير النقدي الحديث، مفيداً من المفهوم العام للقراءة، التي بها تتحقق حياة النص الأدبي وسيرورته. \ فلم يتمكن الباحث تجاوز إعجابه بما قرأ في وعن نظرية "التأويل" الحديثة، ولثقته في ثراء الموروث النقدي والبلاغي العربي، حيث أخذ يبحث عن شيء من ملامح وأبعاد تلك النظرية وتطبيقاتها في مصادر التراث، حتى تبين له أن ذلك مما لا تخطئه العين في كتاب "نقد الشعر". \ ولعل أهم ما شجع الباحث على المضي في هذا الاتجاه، أنه لم يسبق إلى قراءة "نقد الشعر" من هذا المنظور على حد علمه، وبعد اجتهاده في التنقيب والسؤال. \ فالهدف من البحث هو تأصيل نظرية "التأويل" في تراثنا النقدي، والوسيلة هي المنهج الوصفي الذي يتناول الظاهرة بكل أبعادها، والمكتبة هي نقد الشعر قديما وحديثا. \ أما مفردات البحث ومحاوره الرئيسية فستكون في عناوين ثلاثة؛ هي: \ أولا: المهاد النظري، ويتناول مفهوم المصطلح، وآفاق النظرية. \ ثانيا: طبيعة النص الشعري في كتاب "نقد الشعر"، ويعالج أبعاد النظرية النقدية في الكتاب في مجالي الإبداع والتلقي. \ ثالثا: تأويل الشعر وجماليته عند قدامة بن جعفر، من خلال نماذج من قراءاته الشعرية، وممارسته النقدية. The title of this search his intention about affiliation to what might be called reception aesthetic in modem critical thinking, useful from general of reading, Which achieve life of the literary text. \ Searcher have not been overstep admiration his read in and about the Modem Theory about "The Exegesis", Because of his confidence in richer heritage the rhetorical arab critical, Was taking looking for something of the features and dimensions of that theory and its applications in the heritage sources, Until he realized that the things that unmistakable in the book "Poetry Criticism". \ Perhaps the what encouraged the researcher to progress in this direction, Not preceded by one to read the book "Poetry Criticism" from that perspective to his knowledge, And after his diligence in exploration and question. \ And the aim of the research is rooting Theory "The Exegesis" in our heritage critical, And the method is a descriptive approach, which deals with the phenomenon in all its dimensions, And the library, is "poetry Criticism in past and presen". \ The search main axes, will be in three headings: \ Firstly: The boot theoretical, deals with concept of the term, And the horizons of the theory. \ Secondly: The nature of the poetic text in the book "Poetry Criticism", And address the dimensions of of critical theory in this book in the fields of creativity and receiving the poetry. \ Thirdly: The Exegesis poetry "Qudamah Ben Jaafar", Through Models of his poetry readings and his critique.
Keywords: كتاب نقد الشعر -- نقد الشعر -- نظرية التأويل -- النقد الأدبي -- التراث النقدي -- البلاغة العربية -- تأويل الشعر -- قدامة بن جعفر بن قدامة بن زياد، ت . 337 هـ. -- الادب العربي